IMPLEMENTASI SISTEM PENJAMINAN MUTU INTERNAL DI UNIVERSITAS MUHAMMADIYAH METRO LAMPUNG - Garianto Garianto; Yurnalis Etek; Koderi Koderi; Muhammad Ihsan Dacholfany (Edukasi Islami : Jurnal Pendidikan Islam, 2022)
Muhammadiyah Metro University is an Islamic university and the only best private university in Sumatra, according to the International Institute of Webometrics, July 2020. However, some lecturers and students still do not fully understand the existence of quality assurance institutions (LPM) in higher education standards (SPT) that guarantee the quality of higher education, so UM Metro has not achieved its vision and mission optimally. All stakeholders have not fully felt the results of quality assurance (Quality Assurance). This study aims to find out and describe the state of the internal quality assurance system (SPMI) at UM Metro, starting with how to determine, implement, evaluate, control, and improve. Research is qualitative description research with qualitative descriptive analysis. Data is collected employing interviews, documentation, and observations. The results of the research analysis on the implementation of SPMI at UM Metro: through the following stages: 1) Stages of setting standards, vision, mission, regulations, policies, academics, academic quality manuals, and so on in the study program, there is a competence of graduates. 2) The implementation of higher education standards is socialized to all concerned. The importance of a quality education system in implementing higher education is carried out by qualified human resources and leadership support. 3) Evaluation carried out in the implementation of higher education standards starting weekly, monthly, and yearly involving a team of experts under the supervision of LPM. 4) Control, findings from the results of follow-up evaluations that have been well improved by rewarding, and those that have not been well-given guidance according to higher education standards. 5) Improvement, the results of the implementation of previous developments, namely the establishment, implementation, evaluation, and control, are further improved so that users of higher education services feel the results. The implications show that SPMI is very important in universities to achieve a level of excellence in higher education that can be felt by all stakeholders (Stake-HolderS)